COMPARISON OF LISSAMINE GREEN TEST SCORE AND TEAR LIPID FLOATING TIME AMONG NORMAL AND DRY EYE SUBJECTS BASED ON ASIAN DRY EYE SOCIETY (ADES) 2017 DEFINITION - Zainudin, Nurul Shahirah; Ithnin, Mohd Hafidz (International Journal of Allied Health Sciences, 2021)
Aims: The purpose of this study was to compare the lissamine green test score and TLFT between normal and dry eye people who are defined by ADES (2017). Methodology: Forty subjects, consisting of 31 females and 9 males were involved in this quasi-experimental study. Dry eye disease was defined based on the ocular surface disease index (OSDI) of score 33 or more and tear film break-up time (TFBUT) of 5 seconds or less. The assessment of lissamine green and lipid floating time were conducted by using slit lamp videography. Result: TLFT was significantly faster which is about 0.17 seconds lower in the non-dry eye compared to dry eye subjects for both sides of the eyes. While, for lissamine green test, there was no significant difference in lissamine test score of non-dry eye subjects and dry eye subjects. Conclusion: Only tear lipid floating time has correlation with the definition of dry eye disease by ADES 2017. However, the similar trend does not show in lissamine green test hence it can be assumed that the lissamine green test might not have sensitivity with the definition of dry eye disease by ADES 2017. Keywords: Asian Dry Eye Society (ADES) 2017, definition, lissamine green test score, tear lipid floating time, slit lamp videography